The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/adfm.200500655
|View full text |Cite
|
Sign up to set email alerts
|

Au–Pd Alloy Gradients Prepared by Laterally Controlled Template Synthesis

Abstract: Lateral control of template synthesis in nanoporous alumina membranes (NAMs) was previously shown by us to enable preparation of graded composite materials. Formation of thickness gradients of Cu was demonstrated using electrodeposition (or electrodissolution) of Cu in the NAM template under a lateral voltage drop applied to the working electrode. This approach is extended here to the formation of compositional gradients. The latter are achieved by electrochemical co‐deposition of two metals (Au and Pd) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 32 publications
1
16
0
2
Order By: Relevance
“…The membranes were then used as templates for electrodeposition in the pores, such that the open side of the pores is exposed to the solution. Filling of the pores with solution occurs spontaneously after dipping, and, as shown previously, almost all the pores are filled with the deposited material 16,17 …”
Section: Methodssupporting
confidence: 69%
See 3 more Smart Citations
“…The membranes were then used as templates for electrodeposition in the pores, such that the open side of the pores is exposed to the solution. Filling of the pores with solution occurs spontaneously after dipping, and, as shown previously, almost all the pores are filled with the deposited material 16,17 …”
Section: Methodssupporting
confidence: 69%
“…Bohn and coworkers showed that an iR drop created in thin‐film electrodes by injection of in‐plane currents provides means for laterally‐controlled electrochemical manipulation 6 . This approach was applied to the preparation of various laterally inhomogeneous systems and graded materials, such as SAMs displaying spatially‐resolved adsorption of proteins, polymeric coatings showing graded composition and morphology 10–12 including 2D patterning, 13 as well as laterally variable alloy compositions 5,14–16 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…73 Using the same setup, compositional gradients were fabricated, by electrochemical co-deposition of Au and Pd in the membrane, to form an alloy that showed a continuous gradient in Au/Pd ratio. 74 Also hybrid polymer/metal NWs have been fabricated, with a gradient in length of polymer, by first electrodepositing polyaniline while employing an in-plane potential gradient, followed by the electrodeposition of Ag or Cu. 75 Another dynamic display of electrochemical gradients by an in-plane potential gradient was shown by Tada and co-workers.…”
Section: Electrochemical Gradients By An In-plane Potential Gradientmentioning
confidence: 99%